The Application of Reservation Based on Web at Mbah Koboy Cafe - Setya, Muhammad Donny; Rusli, Muhammad (I-STATEMENT, 2018)
The purpose of this research is to build and implement a reservation application to support the business needs of Mbah Koboy Cafe. The problems that exist in the cafe when the number of customers that require waiting to get a place called waiting list. The method used is the prototype method. Applications are created using HTML and PHP programs with MySQL databases. The results of research in the form of Application Reservation Place Mbah Koboy Cafe based on website that is able to make the reservation process where the visitors who come no longer waiting and can display information about the cafe. Then there is the admin page to manage the room and transaction.